HE SOCIAL –PSYCHOLOGICAL SIGNIFICANCE OF GENDER STEREOTYPES IN PREPARING YOUTH FOR FAMIL U LIFE - dots. A.Turg'unboyeva; prof .M.Abdullayeva; PhD. M.Tоshibekova; dots. N.Abdullayeva; Sr. Lecturer G. Mirzatova (The Bioscan, 2024)
In this article, the problem of differences in the development of men and women and its psychological features are widely covered. Also, the specific meaning of gender equality and differences was discussed.